Jurisprudencia española sobre educación para la ciudadanía - Gómez Orfanel, Germán (Anuario de Derechos Humanos. Nueva Época, 2009)
The great political and ideological contest developed in Spain in the last past years, about the implement of Education for Citizenship in undergraduate studies, has been solved in a relevant measure, with the decisions of the Supreme Court in february 2009. This article focuses on the study of such case law and the different positions of the Court members, about subjects such as the objection of conscience and ideological and educational liberties.
Keywords: Civic education; Pluralism; Educational liberty; Ideological liberty; Objection of conscience; Policy of education